A Systematic Review of Fish Protein Hydrolysates in Functional Foods: Balancing Nutritional Fortification with Sensory Acceptance - Salsabila Mega Kencono Ganggi; Ahmad Syauqy; Gemala Anjani; Fitriyono Ayustaningwarno; Widya Rusyanto; Diana Nur Afifah (Media Publikasi Cendekia Indonesia, 2026)
Fish and fish by-products are rich in high-quality protein and bioactive compounds, but their use in value-added food products is still limited. Fish protein hydrolysate (FPH) has outstanding digestibility and functional properties, making it a potential ingredient for food fortification. However, differences in fish species, hydrolysis methods, and fortification levels can affect nutritional quality and sensory acceptance. This literature review aims to synthesize the latest evidence on the impact of adding various types of fish protein hydrolysates to food products, with a focus on nutritional value, physicochemical properties, and sensory characteristics. The literature review was conducted using the ScienceDirect and PubMed databases following the PRISMA approach. Thirteen eligible studies published between 2015 and 2025 were analyzed using descriptive qualitative analysis. The reviewed studies indicated that FPH derived from salmon, tilapia, seabass, anchovy, tuna, cod, sea bream, and mullet consistently increased protein content, improved amino acid profiles, increased antioxidant activity, and, in some cases, improved mineral content and shelf life. Moderate fortification levels (around 5–10%) provided the best balance between nutritional improvement and sensory acceptance, while higher levels tended to cause darker color changes, texture changes, and unpleasant tastes such as bitterness. Fish protein hydrolysates are promising functional ingredients for nutritionally enriched food products. Optimization of hydrolysis methods and fortification levels is necessary to maximize nutritional benefits while maintaining sensory quality. Further research is needed to evaluate bioavailability and long-term health effects, especially in nutritionally vulnerable populations.